Upaya Meningkatkan Pemahaman Konsep Matematika Siswa Dengan Model Pembelajaran Example Non-Example - Suci Charolina; Yasifati Hia (Journal Mathematics Education Sigma [JMES], 2022)
Abstract. This research aimed to improve the understanding of mathematical concepts of SMK Sri Langkat Tanjung Pura’s students by implementing the Example Non-Example learning model through animated videos. This research type was classroom action research. The subject of this research is the students' of class X majoring in TKR SMK Sri Langkat Tanjung Pura. This research occurred in two cycles. The first cycle consisted of two meetings and the second cycle also consisted of two meetings. In this research, the data collection techniques applied were observation, tests, and questionnaires. The instruments used were observation sheets, tests, and learning response questionnaires. While for the data analysis technique, the descriptive quantitative was employed. Based on the observation result,  there were increases in each indicator’s percentage of understanding mathematical concepts from the first cycle and second cycle, which were: 1) Restating that mathematical concept in the first cycle of 90% increased to 93% in the second cycle. 2) Classifying objects according to certain traits did not experience a constant increase of 86%. 3) Creating examples and non-examples in the first cycle of 71% increase to 86% in the second cycle. 4) Presenting concepts in various forms of mathematical representation in the first cycle of 65% increased to 89% in the second cycle. 5) Applying the concept or algorithm problem-solving in the first cycle of 63% increased to 93% in the second cycle. Furthermore, the increase in the average percentage of learning test results from 75.3 in the first cycle with moderate criteria increased to 83.75 in the second cycle with high criteria.Abstract. Penelitian ini bertujuan untuk meningkatkan pemahaman konsep matematika siswa SMK Sri Langkat Tanjung Pura dengan menerapkan model pembelajaran Contoh Non-Contoh melalui video animasi. Jenis penelitian ini adalah penelitian tindakan kelas. Subjek penelitian ini adalah siswa kelas X jurusan TKR SMK Sri Langkat Tanjung Pura. Penelitian ini terjadi dalam dua siklus. Siklus pertama terdiri dari dua pertemuan dan siklus kedua juga terdiri dari dua pertemuan. Dalam penelitian ini, teknik pengumpulan data yang diterapkan adalah observasi, tes, dan kuesioner. Instrumen yang digunakan adalah lembar observasi, tes, dan kuesioner respon pembelajaran. Sedangkan untuk teknik analisis data, digunakan kuantitatif deskriptif. Berdasarkan hasil pengamatan, terdapat peningkatan persentase pemahaman konsep matematika masing-masing indikator dari siklus I dan siklus II, yaitu: 1) Menyatakan kembali konsep matematika itu pada siklus pertama 90% meningkat menjadi 93% pada siklus kedua. 2) Mengklasifikasikan objek sesuai dengan sifat-sifat tertentu tidak mengalami peningkatan konstan sebesar 86%. 3) Membuat contoh dan non-contoh pada siklus I sebesar 71% meningkat menjadi 86% pada siklus II. 4) Menyajikan konsep dalam berbagai bentuk representasi matematis pada siklus pertama 65% meningkat menjadi 89% pada siklus ii. 5) Menerapkan pemecahan masalah konsep atau algoritma pada siklus pertama sebesar 63% meningkat menjadi 93% pada siklus ii. Selanjutnya, peningkatan rata-rata persentase hasil tes pembelajaran dari 75,3 pada siklus I dengan kriteria sedang meningkat menjadi 83,75 pada siklus II dengan kriteria tinggi.